Theatre efficiency in COVID-19 pandemic conditions: The collaborative experience of four level 1 major trauma centres in the UK. (26th October 2021) - Jeyaseelan, Lucky; Sedgwick, Philip; El-Daly, Ibraheim; Tahmassebi, Ramon; Pearse, Michael; Bhattacharya, Rajarshi; Trompeter, Alex J.; Bates, Peter
Abstract : Aims: As the world continues to fight successive waves of COVID-19 variants, we have seen worldwide infections surpass 100 million. London, UK, has been severely affected throughout the pandemic, and the resulting impact on the NHS has been profound. The aim of this study is to evaluate the impact of COVID-19 on theatre productivity across London's four major trauma centres (MTCs), and to assess how the changes to normal protocols and working patterns impacted trauma theatre efficiency. Methods: This was a collaborative study across London's MTCs. A two-month period was selected from 5 March to 5 May 2020. The same two-month period in 2019 was used to provide baseline data for comparison. Demographic information was collected, as well as surgical speciality, procedure, time to surgery, type of anaesthesia, and various time points throughout the patient journey to theatre. Results: In total, 1, 243 theatre visits were analyzed as part of the study. Of these, 834 patients presented in 2019 and 409 in 2020. Fewer open reduction and internal fixations were performed in 2020 (33.5% vs 38.2%), and there was an increase in the number of orthoplastic cases in 2020 (8.3% vs 2.2%), both statistically significant results (p < 0.000). There was a statistically significant increase in median time from 2019 to 2020, between sending for a patient and their arrival to the anaesthetic room (29 vs 35 minutes; p = 0.000). Median time between arrival in the anaesthetic room and commencement of anaesthetic increased (7 to 9 minutes; p = 0.104). Conclusion: Changes in working practices necessitated by COVID-19 led to modest delays to all aspects of theatre use, and consequently theatre efficiency. However, the reality is that the major concerns of impact of service did not occur to the levels that were expected. Cite this article: Bone Jt Open 2021;2(10):886–892.